2023
DOI: 10.1186/s12978-023-01573-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing contraceptive use as a continuum: outcomes of a qualitative assessment of the contraceptive journey

Abstract: Background Contraceptive use is often a multi-decade experience for people who can become pregnant, yet few studies have assessed how this ongoing process impacts contraceptive decision-making in the context of the reproductive life course. Methods We conducted in-depth interviews assessing the contraceptive journeys of 33 reproductive-aged people who had previously received no-cost contraception through a contraceptive initiative in Utah. We coded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…The main themes that were identified were effects, side effects, towards alternatives, interpersonal communication with peers, interpersonal communication with the general practitioner, online information seeking and feeling responsible. There are similarities between the results and those of Simmons et al (2023) [ 13 ]. Simmons et al (2023) assessed the contraceptive journey of participants using interviews and did not specifically focus on OCP use, but mainly on a person's contraceptive journey, and the four phases thereof.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The main themes that were identified were effects, side effects, towards alternatives, interpersonal communication with peers, interpersonal communication with the general practitioner, online information seeking and feeling responsible. There are similarities between the results and those of Simmons et al (2023) [ 13 ]. Simmons et al (2023) assessed the contraceptive journey of participants using interviews and did not specifically focus on OCP use, but mainly on a person's contraceptive journey, and the four phases thereof.…”
Section: Discussionsupporting
confidence: 87%
“…Although aforementioned pros and cons of OCP use have been examined, most studies focus on contraception decisions in general, rather than specifically on OCP decision-making. For instance, in the study of Simmons et al [ 13 ], semi-structured interviews were used to develop a theory of how contraceptive decision-making occurs over time, identifying different phases in a person's contraceptive journey and five main areas of decisional influence within these phases. According to Sato et al [ 14 ], both discontinuation rates and reasons of discontinuation seems to vary by the type of contraception method, highlighting the relevance of specifically investigating OCP use.…”
Section: Introductionmentioning
confidence: 99%
“…A German study on the knowledge and perceptions about OCPs among young women showed that 64.5% (n = 1480) of those who used OCPs at some point discontinued the method [29]. Simmons et al examined the cessation of contraceptive methods as part of a person's Contraceptive Journey [42]. They defined key factors contributing to this decision: physiological factors, values, experiences, circumstances, and relationships (e.g.…”
Section: The Pill and Mainstream Media-a Problematic Relationship?mentioning
confidence: 99%
“…The discontinuation of OCPs deprives the body of an external source of artificial progesterone and estrogen, resulting in a change in the hormone levels in the body [43,44]. Current medical research on OCP discontinuation is limited to fertility restoration [45,46], fecundability [44], cycle characteristics [45,47], and reasons for discontinuation [29,42,48].…”
Section: The Pill and Mainstream Media-a Problematic Relationship?mentioning
confidence: 99%
“…Focusing on use of certain methods in quality and access metrics neglects that users may want to switch or stop using methods, since method discontinuation and switching are inherently part of the dynamic journey of contraceptive use. 13 , 14 , 15 In a 2022 nationally representative survey of adult U.S. women, 25% of contraceptive users indicated a preference for a different method. 16 The most recent National Survey of Family Growth asked respondents what method they would use if cost was not a worry; in 2015–17, 22% of U.S. women who had “heterosexual intercourse” in the last three months and were not pregnant or trying to become pregnant would use a different method, with the highest level of unsatisfied preferences among Black and Latinx women and low-income women.…”
Section: Introductionmentioning
confidence: 99%